Persatuan umat beragama Peace as a Form of Unity of Interfaith Communities in Indonesia - Yusuf, Muhammad Taufiq (Nizham Jurnal Studi Keislaman, 2024)
Peace is a condition in which there is balance and harmony in life, both between individuals and between community groups. Peace can be realized when there is awareness and concrete action to build harmonious and respectful relations between people across religions. Unity of interfaith people is one of the keys to realizing peace. To build interfaith unity, a deep understanding of the values ​​of different religions and the similarity of values ​​among them is needed. This understanding can be realized through dialogue and interaction between religious groups, which can open up space to understand each other's views and beliefs. In addition to dialogue and interaction, there are also concrete efforts that can be made to build interfaith unity, such as cooperation in social, cultural and development activities. By working together in these activities, interfaith people can build trust and eliminate negative prejudices that may exist between them.